2010
DOI: 10.1152/jn.00449.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Graphomotor Sequence Learning: A Combined fMRI and Kinematic Study

Abstract: Swett BA, Contreras-Vidal JL, Birn R, Braun A. Neural substrates of graphomotor sequence learning: a combined fMRI and kinematic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…Altogether, the present experiments suggest an important contribution of the detailed visual analysis in symbol learning and provide no evidence that graphomotor training per se leads to a better encoding or helps to discriminate orientation. The present findings are in line with studies arguing for the importance of stroke units and visual analysis at the onset of learning of new graphomotor sequences (Hulstijn & van Galen, 1988;Portier et al, 1990;Swett et al, 2010), and more generally with the visual conception of letter recognition. This latter conception is supported by neuroimaging studies which assume that letter processing is carried out by a part of the left fusiform gyrus of the extrastriate visual cortex (Flowers et al, 2004;Garrett et al, 2000;James et al, 2005;Polk et al, 2002;Wong et al, 2009), and by most current models of word recognition which postulate that letter recognition is a visual process based on elementary features extraction (Coltheart et al, 2001;Grainger et al, 2008;McClelland & Rumelhart, 1981;Perry et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Altogether, the present experiments suggest an important contribution of the detailed visual analysis in symbol learning and provide no evidence that graphomotor training per se leads to a better encoding or helps to discriminate orientation. The present findings are in line with studies arguing for the importance of stroke units and visual analysis at the onset of learning of new graphomotor sequences (Hulstijn & van Galen, 1988;Portier et al, 1990;Swett et al, 2010), and more generally with the visual conception of letter recognition. This latter conception is supported by neuroimaging studies which assume that letter processing is carried out by a part of the left fusiform gyrus of the extrastriate visual cortex (Flowers et al, 2004;Garrett et al, 2000;James et al, 2005;Polk et al, 2002;Wong et al, 2009), and by most current models of word recognition which postulate that letter recognition is a visual process based on elementary features extraction (Coltheart et al, 2001;Grainger et al, 2008;McClelland & Rumelhart, 1981;Perry et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a recent study reported stronger activation of the visual regions during the early stage of learning new graphomotor sequences than later on. This visual activation occurred in conjunction with premotor activation and was assumed to reflect the visuomotor mapping process which transforms visuospatial signals into motor commands (Swett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of procedural learning, the Bassociative^portions of the caudate nucleus appear to be involved in early phases of learning, while the Bmotor^puta-men is more prominently engaged when animals execute previously learned movement sequences [109][110][111][112][113][114][115][116][117][118]. Hypotheses about the role of dopamine in reinforcement learning are closely tied to the finding that dopamine neurons fire in relation to (positive) prediction errors in rewarded tasks [119][120][121][122][123][124][125].…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 99%
“…Our inclusion criteria for the studies were the following: (1) that brain scanning was performed using either functional magnetic resonance imaging or positron emission tomography; (2) that papers reported activation foci in the form of standardized stereotaxic coordinates in either Talairach or Montreal Neurological Institute (MNI) space; (3) that subjects were healthy adults (thereby excluding results from clinical populations as well as children); (4) that subjects performed tasks that conformed with the above mentioned definitions of drawing and writing; (5) that results from the entire scanned brain volume were reported, thereby excluding studies having partial brain coverage, that reported activation data for only specific areas, or that only reported region-of-interest analyses (Longcamp et al, 2003;Menon & Desmond, 2001); (6) that a writing task involve the use of a writing tool, rather than typing on a keyboard; and (7) that the experiment focus on the sensorimotor aspects of drawing and writing rather than on higher-order processes, such as learning (Frutiger et al, 2000;Swett, Contreras-Vidal, Birn, & Braun, 2010), creative drawing, or creative writing. Regarding the last criterion, two writing papers performed multiple high-level contrasts so as to remove either the motor activity of hand movements or linguistic processing of the semantic aspects of the stimuli (Beeson et al, 2003;Katanoda, Yoshikawa, & Sugishita, 2001).…”
Section: Search Query and Inclusion Criteriamentioning
confidence: 99%